Pendampingan Pemberdayaan Masyarakat dalam Pengelolaan Sampah, Pencegahan Stunting, dan Pengendalian Hipertensi di Kelurahan Cabenge, Kabupaten Soppeng: Pendampingan Pemberdayaan Masyarakat dalam Pengelolaan Sampah, Pencegahan Stunting, dan Pengendalian Hipertensi di Kelurahan Cabenge, Kabupaten Soppeng - Acha, Muhammad Arsyad; Riskiyani, Shanti; Rahma.Ss, Alya Muftia; Rismayana, Rismayana; Fauzi Rachman, Langkar Diyang (Jurnal Pengabdian Kesehatan Komunitas, 2026)
This community service program aimed to empower the community in waste management, stunting prevention, and hypertension control through asset-based community development (ABCD) and human-centered design (HCD) approaches. The activity was conducted from January 5–19, 2026, in Cabenge Village, Soppeng Regency, involving 15–28 participants per session, including village officials, health cadres, community leaders, midwives, and residents. Methods included focus group discussions, asset mapping (six asset categories), root cause analysis using fishbone diagrams, and collaborative action plan development. Results indicated that the root cause of waste management problems was the absence of a community-based system with adequate facilities. Stunting was caused by low family knowledge and practices in child nutrition and care. Hypertension was caused by unhealthy lifestyles and low awareness of early detection. Asset mapping identified local potentials, including health cadres, posyandu, puskesmas, moringa and papaya plants, sphygmomanometers, and mutual cooperation traditions. The program concludes that integrating ABCD and HCD approaches effectively identifies root causes and maps local assets for sustainable health interventions. Abstrak Kegiatan pengabdian ini bertujuan memberdayakan masyarakat dalam pengelolaan sampah, pencegahan stunting, dan pengendalian hipertensi melalui pendekatan Asset-Based Community Development (ABCD) dan Human-Centered Design (HCD). Kegiatan dilaksanakan 5–19 Januari 2026 di Kelurahan Cabenge, Kabupaten Soppeng, dengan 15–28 peserta setiap pertemuan (aparat kelurahan, kader kesehatan, tokoh masyarakat, bidan, warga). Metode: FGD, pemetaan aset (6 kategori), analisis fishbone, dan penyusunan rencana aksi. Hasil: akar masalah sampah adalah belum adanya sistem berbasis masyarakat; stunting disebabkan rendahnya pengetahuan gizi keluarga; hipertensi akibat gaya hidup tidak sehat. Pemetaan aset mengidentifikasi kader, posyandu, puskesmas, kelor, pepaya, tensimeter, dan gotong royong. Kegiatan menyimpulkan integrasi ABCD dan HCD efektif mengidentifikasi akar masalah dan memetakan aset lokal untuk intervensi berkelanjutan.